PEMBERDAYAAN MASYARAKAT PETANI PADI DI DESA ANAK SETATAH KECAMATAN RANGSANG BARAT KABUPATEN KEPULAUAN MERANTI TAHUN 2019 - Ria Indriyani; Sofyan Hadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT In Law Number 6 Article 26 of 2014 concerning Villages it is stated that the village government carries out village development, fostering village communities and empowering village communities and has the authority to increase. village economy and integrate it in order to achieve a productive scale economy for the greatest possible prosperity of the village community. The purpose of this study was to determine the empowerment of the rice farming community in Anak Setatah Village, Rangsang Barat District, Meranti Islands Regency in 2019 and to find out what inhibiting factors or obstacles in empowering the rice farming community in Anak Setatah Village, Rangsang Barat District, Meranti Islands Regency in 2019 The results of this study indicate that the empowerment of the rice farming community in Anak Setatah Village, Rangsang Barat District, Meranti Islands Regency in 2019 was carried out by providing assistance and counseling to rice farmers regarding procedures for rice cultivation, post-harvest land processing and harvest processing, as well as empowerment activities carried out with the Establishment of the Association of Farmers Groups. The inhibiting factor for empowering the rice farming community in Anak Setatah Village, Rangsang Barat sub-district, Meranti Islands district in 2019 was the lack of human resources and supporting assistance for the community. Keywords:Preparation Stage, Assesment Stage, Planning Stage, Implementation Stage, Evaluation Stage.